2010
DOI: 10.1007/s11626-010-9297-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of defined culture systems for feeder cell free propagation of human embryonic stem cells

Abstract: There are many reports of defined culture systems for the propagation of human embryonic stem cells in the absence of feeder cell support, but no previous study has undertaken a multi-laboratory comparison of these diverse methodologies. In this study, five separate laboratories, each with experience in human embryonic stem cell culture, used a panel of ten embryonic stem cell lines (including WA09 as an index cell line common to all laboratories) to assess eight cell culture methods, with propagation in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(122 citation statements)
references
References 29 publications
3
119
0
Order By: Relevance
“…These results are coherent with the general morphology of hESCs grown on Matrigel and CELLstart, in which the absence of feeders is associated with flatter colony morphology, and in the case of CELLstart, looser cell-cell contacts as evidenced by additional cell spreading (Fig. S1A) (5). With respect to medium formulation, commensurate expression responses are noted in Table S4.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These results are coherent with the general morphology of hESCs grown on Matrigel and CELLstart, in which the absence of feeders is associated with flatter colony morphology, and in the case of CELLstart, looser cell-cell contacts as evidenced by additional cell spreading (Fig. S1A) (5). With respect to medium formulation, commensurate expression responses are noted in Table S4.…”
Section: Resultssupporting
confidence: 84%
“…Matrigel is derived from mouse sarcomacell extracts and is highly enriched in extracellular matrix (ECM) components and a variety of growth factors (5). CELLstart is a humanized substrate considered to be the first xeno-free option for hESC cultures (5). Both STEMPRO and mTesR1 media are complex formulations that use FGF-and TGF-β-signaling pathways to maintain pluripotency.…”
mentioning
confidence: 99%
“…S4), although the progression appeared more efficient in our hands (∼70% in 5 d) than as described by Bernardo et al (21), in which only 4-8% of the cells became KRT7 + after a comparable time of exposure to BMP4 in a medium lacking the basal amount of FGF2 (12 ng/mL) and Activin (10 ng/mL). The International Stem Cell Initiative Consortium has tested the CDM used by Bernardo et al (21) and demonstrated that it performed poorly in independent tests carried out by five independent laboratories (33). In each comparison, the majority of hESC lines showed either considerable cell death or spontaneous differentiations within three passages when cultured on the CDM used by Bernardo et al; only MEF-CM, mTeSR1, and a third medium, STEMPRO, successfully maintained all lines in a pluripotent state for at least 10 passages.…”
Section: Discussionmentioning
confidence: 99%
“…They are also perfectly fitted to allow practical and cost-effective quality controls. Standards have been established for pluripotent stem cells both for biological identification [21] and for banking [22], and consensus for culture conditions has also been reached [23]. Automation of cultures, using standardized feeder-free conditions, will clearly reduce the batch to batch variations that unavoidably mar all manual processes.…”
Section: Meeting the Prerequisite Of Industrializationmentioning
confidence: 99%